PERENCANAAN KURIKULUM SEKOLAH DAN MADRASAH - Muhamad Husni (Jurnal Tata Kelola Pendidikan, 2021)
This study aims to determine curriculum planning, supporting and inhibiting factors in curriculum planning in SMAN 1 Singaparna and MAN 2 Tasikmalaya. The results of this study showed that curriculum planning at SMAN 1 Singaparna and MAN 2 Tasikmalaya was carried out by a curriculum development team consisting of principals or madrasas, deputy heads, teachers, administrative staff, committees, and education supervisors by taking five basic frameworks, namely needs analysis, goal development, content development, learning activities, and evaluation of curriculum planning. Curriculum planning in SMAN 1 Singaparna is supported by the quality of the teachers and administrative staff and the completeness of the facilities, but is hampered by some teachers who still have a traditional-manual mindset, administrative complexity, and an incomplete understanding of 21st century education patterns. While the supporting factors in MAN 2 Tasikmalaya are the quality of teachers and administrative staff, completeness of the facilities, strict selection of students, and boarding school cooperation. However, this madrasa faces resistances from the mindset of some teachers and time management for students who live in the boarding school.